PERILAKU MASYARAKAT DALAM MENGGUNAKAN MEDIA DIGITAL DI MASA PANDEMI - Nani Sintiawati (Jurnal AKRAB, 2020)
Indonesia is one of the countries affected by the Covid-19 outbreak. The government’s policy regarding Large-Scale Social Restrictions (PSBB) has an impact on various sectors in Indonesia, be it the economic, entertainment, religious and educational sectors. The need to understand the use of digital media in society greatly determines the mindset of society in dealing with this pandemic. Educational activities that were stopped during the pandemic were transformed into online learning using digital media. Ease of accessing all information can be obtained through several applications in gadgets in people’s lives, but not all people take advantage of these opportunities positively. The purpose of this study was to determine people’s behavior in using digital media during the Covid-19 pandemic. The research method used is the literature review method based on literature exploration from the results of previous studies. These literatures are in the form of books, survey results, online media, and national research articles. The research results reveal that there have been major changes in people’s behavior in several aspects. The change comes from one’s own initiative as well as an appeal or order from the competent authority. In addition, the pandemic affects the mental and psychological health of the community. Media has always been a social institution, during this pandemic, learning can be carried out using various platforms, both in the form of a learning management system and in the form of video conferencing so that parents and teachers are required to have digital literacy skills. The conclusion of the study is that the use of digital media greatly affects people’s behavior, besides that the ability to use digital media is needed by the community as a digital literacy effort during the Covid-19 pandemic. AbstrakIndonesia termasuk salah satu negara yang terkena dampak wabah covid-19. Kebijakan pemerintah mengenai PSBB memberikan dampak terhadap berbagai sektor di Indonesia, baik itu sector ekonomi, hiburan, keagamaan dan pendidikan. Perlunya pemahaman literasi digital di masyarakat sangat menentukan pola pikir masyarakat dalam menghadapi pandemic ini. Kegiatan pendidikan yang dihentikan selama masa pandemi ini, dirubah dalam bentuk pembelajaran daring dengan memanfaatkan media digital. Kemudahan mengakses segala informasi dapat didapatkan melalui beberapa aplikasi dalam gadget di kehidupan masyarakat, namun tidak semua masyarakat memanfaatkan peluang tersebut secara posisitif. Tujuan penelitian ini untuk mengetahui peranan literasi digital dalam kehidupan masyarakat di masa pandemic covid-19.metode penelitian yang dipakai adalah metode deskripstif mellaui pendekatan kualitatif fenomenologi, penelitian ini dilakukan selama masa beberapa bulan setelah adaptasi kebiasaan baru. Hasil penelitian mengungkapkan bahwa kebiasaan masyarakat di masa pandemic covid-19 adalah mayoritas melakukan hal yang sama yaitu memesan makanan, berbelanja secara online, juga sering berolahraga dan memulai berkebun. Kemudian keluarga menjadi tolak ukur keberhasilan meningkatkan literasi digital untuk anggota keluarganya dengan memanfaatkan akses internet melalui media digital secara bijak. Selain itu keluarga memiliki tanggungjawab memotivasi anggota keluarga untuk menggali bahan bacaan secara digital dan tidak terjebak dalam penyebaran informasi yang tidak benar. Kesimpulan penelitian ialah literasi digital sangat berperan dalam kehidupan masyarakat pada masa pandemic covid-19.